Corrosion performance of 3%Cr steel in CO2‐H2S environment compared with carbon steel. Issue 11 (13th March 2015) - Liu, W.; Lu, S.‐L.; Zhang, Y.; Fang, Z.‐C.; Wang, X.‐M.; Lu, M.‐X.
<x xml:space="preserve">Abstract</x> Corrosion behavior of 3wt.% Cr low alloy steel in aqueous CO2‐H2S environment was investigated in comparison with API X60 carbon steel using high temperature and high pressure autoclave. The corrosion performance of 3Cr steel was analyzed by XRD, XPS, SEM, EDS and EIS. In CO2‐H2S environment, the corrosion scale of 3Cr steel possessed a triple structure of the outer layer of FeS, the middle layer of FeCO3 and the inner layer of FeCO3, Cr(OH)3 and Cr2O3. FeS mainly formed through the dissolution and re‐deposition from FeCO3. Hydrolytic action of Cr3+ during corrosion affected the formation process of corrosion scale of 3Cr steel. The Cr‐rich layer of the corrosion scale of 3Cr steel blocked the ions transport through corrosion scale to improve corrosion resistance of 3Cr steel. For H2S‐containg CO2 environment, 3Cr steel still exhibited higher corrosion resistance than X60 carbon steel and would be a promising material option in such environment.